Comparative Analysis of MVISS and VCS in Secure Image Sharing - Sugianto Sugianto (Politeknik Ganesha Medan, 2025)
This study compares two prominent methods in secure image sharing: Multiparty Verification in Image Secret Sharing (MVISS) and Traditional Visual Cryptography (VCS). MVISS integrates cryptographic techniques such as hash functions (SHA-256) and public-key encryption (RSA) to verify the authenticity of image shares, ensuring secure reconstruction without pixel expansion. In contrast, VCS relies on pixel expansion and manual stacking for decryption, lacking verification mechanisms. Our analysis highlights that MVISS offers superior security and lossless reconstruction, while VCS remains simpler but less secure. The findings suggest that MVISS is more suitable for applications requiring high security, such as biometric data protection and cloud storage, whereas VCS is better suited for low-complexity scenarios.